Annual Energy Efficiency Analysis and Experiment Research on Variable Speed Air-Conditioner Based on Climatic Factors - Li Tang; Wang Fang; Qu Yan; Meng Zhaofeng; Wang Yu; Zhao Yale; Guo Chao (Zhileng xuebao)
Research on the annual performance factor specified in variable speed air-conditioner energy efficiency standard GB21455-2013. A variable speed air-conditioner was studied, two operating modes were established combining with typical meteorological year data. With the experiment and calculation, the air conditioner SEER and HSPF in different cities and different modes were obtained. The running time cumulative rate of temperature range was introduced and relationships between SEER, HSPF and TAS were analyzed, the results show enhancing the air conditioner energy efficiency should focus on improving the different temperature range segment. The APF of each city, each mode and standard GB/T7725-2004 and GB21455-2013 were calculated, the relationships between SEER, HSPF and APF were analyzed. The results show cooling and heating temperature occurrence time specified in the standard do not fully reflect the actually APF of variable speed air-conditioner running at different regions of China and enhancing APF must focus on improving the HSPF.